2001
DOI: 10.1111/j.1752-7325.2001.tb03369.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Fluoride Intake from Birth to 36 Months

Abstract: There is considerable variation in fluoride intake across ages and among individuals. Longitudinal studies may be necessary to fully understand the relationships between fluoride ingestion over time and development of fluorosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
157
1
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 140 publications
(173 citation statements)
references
References 22 publications
(17 reference statements)
12
157
1
2
Order By: Relevance
“…The level of mean fluoride intake (0.35 mg/day at 3 years old) from foods, beverages and dentifrices in this study was found to be lower than that (0.63 mg/day at 36 months old) from water, supplements and dentifrice in fluoridated areas in the US [Levy et al, 2001], and none of the children exceeded the upper intake level designated by the Institute of Medicine of the US National Academy of Science to avoid the risk of dental fluorosis (1.3 mg/day in 1-to 3-year-olds; 2.2 mg/day in 4-to 8-year-olds). Though the mean amount of intake was less than the AI (0.7 mg/day in 1-to 3-year-olds; 1.1 mg/day in 4-to 8-year-olds), some children were estimated to reach the AI.…”
Section: Total Fluoride Intake From Diet and Dentifricementioning
confidence: 85%
“…The level of mean fluoride intake (0.35 mg/day at 3 years old) from foods, beverages and dentifrices in this study was found to be lower than that (0.63 mg/day at 36 months old) from water, supplements and dentifrice in fluoridated areas in the US [Levy et al, 2001], and none of the children exceeded the upper intake level designated by the Institute of Medicine of the US National Academy of Science to avoid the risk of dental fluorosis (1.3 mg/day in 1-to 3-year-olds; 2.2 mg/day in 4-to 8-year-olds). Though the mean amount of intake was less than the AI (0.7 mg/day in 1-to 3-year-olds; 1.1 mg/day in 4-to 8-year-olds), some children were estimated to reach the AI.…”
Section: Total Fluoride Intake From Diet and Dentifricementioning
confidence: 85%
“…In brief, 1305 white US children aged 3 to 12 yrs were recruited from the Center for Oral Health Research in Appalachia (PITT) (Polk et al, 2008;Wang et al, 2010), the Iowa Fluoride Study (IFS) (Levy et al, 2001Marshall et al, 2003;Franzman et al, 2004), and the Iowa Head Start Study (IHS). All participants provided assent with written parental informed consent, and all study procedures were approved by Institutional Review Boards at the pertinent Universities.…”
Section: Methodsmentioning
confidence: 99%
“…fluoridated areas in many countries, as well as in Brazil 5,11,18,23 . This has been attributed to an increase in the fluoride level of foods and beverages through processing with fluoridated water, to the inadvertent ingestion of fluoride toothpaste, and to the inappropriate use of dietary supplements 19 .…”
Section: Introductionmentioning
confidence: 99%